Pengaruh Menonton Film Islam Terhadap Motivasi Melakukan Sholat Lima Waktu Siswa - Ade Fadli Fachrul; Djoko Susilo (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2016)
This research was aimed to determine the effect of watching movies Islam against student religious behavior. While the specific goal is to determine the influence in motivating students to perform the obligatory prayers five times a day. Quantitative methods were used in this study is experimental. The population to be studied is the class X SMK Negeri 47 Jakarta. Selection of a sample of 72 students performed using simple random sampling method. Data collected by field research, and dissemination of the enclosed questionnaire respondents. The conclusion was that there is a strong influence among Islamic movies to motivation to perform their prayers five times a day.